M-mode echocardiographic values in a cohort of young healthy individuals. Issue 1 (January 2015) - Grossman, Alon; Benderly, Michal; Prokupetz, Alex; Gordon, Barak; Kalter-Leibovici, Ofra
Abstract : Objectives: To determine normal M-mode values in healthy young adults and to evaluate whether these values differ among those in whom echocardiography was performed routinely and those in whom echocardiography was performed based on clinical grounds. Methods: A cross-sectional study evaluating a large cohort of young academy applicants of the Israeli air force in the years 1994–2010. Studies were divided into those performed routinely and those performed because of abnormal ECG or physical examination findings. Echocardiographic variables were compared between the two groups and values are expressed as mean ± SD. Results: Echocardiography was performed routinely in 3525 applicants (age 18.5 ± 1.0 years) and following a clinical referral in 3517 applicants (age 18.2 ± 0.9 years). Those in whom echocardiography was performed routinely had slightly higher left ventricular end-systolic diameter (31.2 ± 3.3 vs. 30.7 ± 3.4 mm; P < 0.0001) and aortic root diameter (28.5 ± 2.1 vs. 27.9 ± 2.2 mm; P < 0.0001), and slightly lower left ventricular mass index (108.8 ± 15.8 vs. 109.9 ± 16.5 g/m 2 ; P = 0.005). No differences were noted between the two groups in left atrial diameter, left ventricular end-diastolic volume, posterior wall thickness and interventricular septum thickness. Conclusion: Certain M-mode characteristics may differ (although to a slight degree) in young healthy individuals with electrocardiographic and physical findings compared with those with normal physical examination and electrocardiography.